Magnificat octo tonorum - Ceballos, Rodrigo de, approximately 1530-1581 (Ediciones Uniandes, 2016)
The cycle of magnificats of the composer Rodrigo de Ceballos is a musical treasure of the Spanish Renaissance that is complete only in the Musical Archive of the Cathedral of Bogotá, Colombia. Although Ceballos never traveled to the New World, his music was played over several centuries in the Cathedral and for this reason it survives completely only there.